Ghost Face on a Left Atrial Thrombus in a Young Lady of Bangladesh ! ! ! (Cardiovascular Journal, 2012)
A 36 years old married female with children from a district of Bangladesh had been suffering from mitral stenosis with atrial fibrillation ( AF) with left atrial (LA) thrombus & active pulmonary tuberculosis under anti-TB drugs. She presented with shortness of breath ( SOB), blood mixed sputum & right lower limb pain for 14 days which was later diagnosed as thromboembolism with acute limb ischemia. LA clot was removed by open heart surgery. Three masses of clots were removed, one ball thrombus, another irregular mass taking the shape of LA appendage and the other is a mixture of old and fresh thrombus. Patient underwent mitral valve replacement (MVR). One side of the irregular thrombus showed the impression of a human face (? Ghost). Histopathology confirmed them as thrombi. Patient was discharged home on the 8th post operative day. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12283 Cardiovasc. j. 2012; 5(1): 120-122